Moda e design: relações materializadas e coleção inspirada em Toulouse-Lautrec, Moulin Rouge e suas musas - Gabardo, Vanessa Lisboa (2012)
The objective of this work is to build a fashion collection inspired by Toulouse- Lautrec, Moulin Rouge and their muses. For their development, a methodology of product design was used and adapted to the world of fashion taking into account the specificities of this segment. Thus, the work shows these steps to build a collection that result in twenty ¨looks¨ materialized in sketches. To complete the process of making a collection of one “looks” was made along with a catalog to display the work.